COMPARISON OF LEAVES MORPHOLOGY AND STOMATAL CHARACTERISTICS OF FRANGIPANI (Plumeria acuminata) IN POLLUTED AND NOT POLLUTED PLACE - Imam Mudakir; Pujiastuti Pujiastuti; Iis Nur Asyiah; Siti Murdiyah; Ika Lia Novenda (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
Leaves are an important organ for plants. One part of leaf is stomata which function as a place for gas exchange. The method used in this research is the observation of the morphology and anatomy of frangipani leaves (Plumeria acuminata) which are exposed to pollution and not exposed to pollution. The purpose of this study was to determine environmental conditions or as a bioindicator by observing damage to plants. Macroscopic damage to plants in leaf morphology and microscopic damage to changes in leaf stomata conditions. Observations show that the morphology of frangipani leaves (Plumeria acuminata) which are not exposed to pollution is larger than frangipani leaves (Plumeria acuminata) which are exposed to pollution. The number of stomata in the abaxial part is more than the adaxial part. Meanwhile, the number of stomata on frangipani leaves (Plumeria acuminata) that were not exposed to pollution was more than those exposed to pollution. The stomata type on frangipani leaves (Plumeria acuminata) is anomocytic type with kidney-shaped covering cells.